2014
DOI: 10.1364/boe.5.003660
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of endoscopic Cerenkov luminescence imaging system: in vitro and pseudotumor studies

Abstract: By integrating the clinically used endoscope with the emerging Cerenkov luminescence imaging (CLI) technology, a new endoscopic Cerenkov luminescence imaging (ECLI) system was developed. The aim is to demonstrate the potential of translating CLI to clinical studies of gastrointestinal (GI) tract diseases. We systematically evaluated the feasibility and performance of the developed ECLI system with a series of in vitro and pseudotumor experiments. The ECLI system is comprised of an electron multiplying charge c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…It has been shown that, it is possible to detect the organs within the body by using optical fibers and a CCD camera [54], as well as enable endoscopic testing [55,56]. These studies led to introduction of CLE systems which have apparently high sensitivity and resolution and consist of an optical fiber connect to a CCD sensitive camera which can be used as a helpful tool during the cancer surgery [16] (Fig.…”
Section: čErenkov Luminescence Endoscopy (Cle)mentioning
confidence: 99%
“…It has been shown that, it is possible to detect the organs within the body by using optical fibers and a CCD camera [54], as well as enable endoscopic testing [55,56]. These studies led to introduction of CLE systems which have apparently high sensitivity and resolution and consist of an optical fiber connect to a CCD sensitive camera which can be used as a helpful tool during the cancer surgery [16] (Fig.…”
Section: čErenkov Luminescence Endoscopy (Cle)mentioning
confidence: 99%
“…Due to a small aperture of endoscope and transmission attenuation of optical fibers, there is great attenuation for the CLE system, resulting in relatively low detection sensitivity of radiotracers. 9 There are three possible ways to improve the detection sensitivity of the CLE system. One is to develop a fiber endoscope with an enlarged aperture.…”
mentioning
confidence: 99%
“…13 The radiotracer and CLE system used here are the same as in our previous study. 9 The radionuclide 68 Ga is in the form of 68 produced by a 68 Ge-68 Ga generator (ITG Isotope technologies Garching GmbH, Germany). The CLE system is a seamless combination of an electron multiplying CCD (EMCCD) camera (iXon3 888, Andor), an optical adaptor (Outai Corp), and a fiber endoscope (GIF-XQ40, Olympus), which is used to collect the emitted luminescence from the mixture of 68 Ga and Gd 2 O 2 S:Tb.…”
mentioning
confidence: 99%
See 2 more Smart Citations